Environmental health risks perceptions: results from cross-sectional surveys in Southeastern France. (13th November 2019) - Bocquier, A; Cortaredona, S; Andrieu-Semmel, M; Dagnet, L; Pouget, V; Urban-Boudjelab, S; Verger, P
Abstract: Background: In accordance with commitments made as part as the European conferences on environment and health in the 90s, France has adopted national environmental health plans since 2004. These plans include regional offshoots to take local specificities into account. To guide stakeholders in defining this plan in Southeastern France, studies were carried out to document general population environmental health risks perceptions and practices. Methods: Data come from the Southeastern Baromètre santé environment, random cross-sectional telephone surveys carried out in 2007 and 2017 among the population aged 18-75 years (n = 1415 and 1960 respectively). They focused on people perceptions' about environmental health risks (e.g., air pollution) and actions to reduce them, trust in sources of information, and their practices. We performed descriptive analyses of the 2017 data, and logistic regression models adjusted for sociodemographic variables to test time evolutions. Results: In 2017, the main environmental health risks perceived were pesticides, carbon monoxide, and air pollution (over 90% of the participants thought they carry high health risks). As in 2007, over 90 % thought the air quality had been worsening. The most efficient ways to reduce air pollution were the improvement of public transportation, of bike paths and the development of car sharing. Between 2007 and 2017, self-reported use of soft mobility and/or car sharing increased from 54% to 66%; and consumption of organic food increased from 40% to 69%. Participants perceived physicians as the most trustful source of information about environmental health. Conclusions: Habitants from Southeastern France are highly concerned by environmental health risks, especially pesticides and air pollution. They call stakeholders to take actions to reduce these risks, but appear to have changed some of their own practices too. These results helped stakeholders to define priorities of the current regional environmental health plan. Key messages: The general population was highly concerned by environmental health risks (especially pesticides and air pollution), and has become aware of the necessity of changing its own practices. Such results about the regional population main concerns have been used to define regional priorities for actions.